Towards new ways of terminology description : the sociocognitive-approach - Temmerman, Rita (Terminology and lexicography research and practice ;, 2000)
Based on an empirical study of categorisation and lexicalisation processes in a corpus of scientific publications on the life sciences, Rita Temmerman questions the validity of traditional terminology theory. Her findings are that the traditional approach impedes a pragmatic and realistic description of a large number of categories and terms. Inspired by the cognitive sciences, she develops an alternative. The main principles of this new theory imply: a combined semasiological and onomasiological perspective; only few categories can be clearly delineated; form and content of definitions vary a.